(untitled) (Experimental biology, 2016)
The article presents the results of a study of heavy metals (Zn, Mn, Co, Ni) in the samples of plants collected in the territory of Atyrau region. Sampling of plants produced in three locations: №1 point (Atyrau, farm "Ulan"), №2 point (Kulsary, p. Turgysba, farm) and №3 n. Inder (farm "Isayev"). It was found that the content of heavy metals in all samples, both in the soil and in the plants did not exceed MPC. The greatest number of heavy metals accumulated in the samples of plants collected in the city of Atyrau (farm "Ulan"). It was revealed that in the same environmental conditions of Atyrau region in selected samples of the dominant plant Artemisia terrae-albae content of heavy metals was higher than that of Agropyron repens.